2020
DOI: 10.1016/j.molcel.2020.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Deubiquitination and Acetylation of SPRTN Promotes DNA-Protein Crosslink Repair and Protects against Aging

Abstract: DNA-protein crosslinks (DPCs) are highly toxic DNA lesions that threaten genomic integrity. Recent findings highlight that SPRTN, a specialized DNA-dependent metalloprotease, is a central player in proteolytic cleavage of DPCs. Previous studies suggest that SPRTN deubiquitination is important for its chromatin association and activation. However, the regulation and consequences of SPRTN deubiquitination remain unclear.Here we report that, in response to DPC induction, the deubiquitinase VCPIP1/VCIP135 is phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 37 publications
(73 reference statements)
1
42
0
1
Order By: Relevance
“…Of note, while this study was under consideration, it was proposed that SPRTN is deubiquitylated by VCPIP1 ( 29 ). In addition, a recent preprint argued that USP11 is responsible for SPRTN deubiquitylation ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, while this study was under consideration, it was proposed that SPRTN is deubiquitylated by VCPIP1 ( 29 ). In addition, a recent preprint argued that USP11 is responsible for SPRTN deubiquitylation ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…DPC proteases can themselves be modified for regulatory purposes. SPRTN exists in a mono-ubiquitylated form, but exposure to FA leads to its de-ubiquitylation—two different studies have identified the de-ubiquitylating enzymes VCPIP and USP11—and acetylation to allow recruitment to chromatin 4 , 64 , 65 .…”
Section: Dpc Proteasesmentioning
confidence: 99%
“…VCPIP1 was also a strong hit implicated in DNA repair. VCPIP1 is a deubiquitinase that is activated by ATM/ATR and involved in the removal of protein-DNA crosslinks through the regulation of SPRTN, that is critical for damage prevention during DNA replication[70,71]. In addition, the gene encoding the Protein phosphatase 2A subunit (PPP2R2A) was negatively selected.…”
Section: Resultsmentioning
confidence: 99%